BMPR2 Editing in Fibroblast NIH3T3 using CRISPR/Cas9 Affecting BMPR2 mRNA Expression and Proliferation - Dwi Aris Agung Nugrahaningsih; Eko Purnomo; Widya Wasityastuti; Ronny Martien; Nur Arfian; Tety Hartatik (The Prodia Education and Research Institute (PERI), 2022)
BACKGROUND: Bone Morphogenetic Protein Receptor II (BMPR2) deficiency is associated with the pathologic development of pulmonary vascular changes in Pulmonary Arterial Hypertension (PAH). Fibroblast is the most abundant cell in vascular. However, there is only a little information regarding the effect of BMPR2 deficiency in fibroblast. This study aims to understand the effect of BMPR2 deficiency in fibroblasts.METHODS: This study applied the CRISPR/Cas9 technique to edit BMPPR2 in NIH-3T3 cells. The transfection of CRISPR/Cas9 for BMPR2 editing into NIH-3T3 cells was done by using chitosan nanoparticles. The evaluation of BMPR2 and Transforming Growth Factor (TGF)-β mRNA expression was done using Quantitative real-time polymerase chain reaction. The assessment of edited NIH-3T3 cells proliferation was done using a scratch test assay.RESULTS: The BMPR2 mRNA expression of CRISPR/Cas9-edited group was lower than the untreated group. The proliferation of the CRISPR/Cas9-edited group was higher than the untreated group. The TGF-β mRNA expression of CRISPR/Cas9-edited and untreated groups was similar.CONCLUSION: BMPR2 deficiency in fibroblast increase the fibroblast ability to proliferate.KEYWORDS: BMPR2, PAH, fibroblast NIH-3T3, CRISPR/Cas9, proliferation